Perceived Concerns and Advocated Organisational Structures of Ownership Supporting ‘Offshore Wind Farm – Mariculture Integration’ - Krause, Gesche; Griffin, Robert Maurice; Buck, Bela Hieronymus (IntechOpen, 2011)
None